2017
DOI: 10.4313/teem.2017.18.1.21
|View full text |Cite
|
Sign up to set email alerts
|

A Study on an Oxygen Vacancy and Conductivity of Oxide Thin Films Deposited by RF Magnetron Sputtering and Annealed in a Vacuum

Abstract: Usually, the oxygen vacancy is an important factor in an oxide semiconductor device because the conductivity is related to the oxygen vacancy, which is formed at the interface between oxide semiconductors and electrodes with an annealing processes. ZTO is made by mixing n-type ZnO and p-type SnO 2 . Zink tin oxide (ZTO), zink oxide (ZnO) and tin oxide (SnO 2 ) thin films deposited by RF magnetron sputtering and annealed, to generate the oxygen vacancy, were analyzed by XPS spectra. The contents of oxygen vacan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 18 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…The threshold voltage (V TH ) showed negative shifts as the increase in the In contents of the channel, which typically suggests that the conduction carriers might be additionally generated within In-richer IGZO channels. 13,21 The highest μ FE was obtained to be 36.9 cm 2 /(V s) for the Dev. C. It was noticeable that there were marked differences in μ FE between the devices using ITO and Mo S/D electrodes.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The threshold voltage (V TH ) showed negative shifts as the increase in the In contents of the channel, which typically suggests that the conduction carriers might be additionally generated within In-richer IGZO channels. 13,21 The highest μ FE was obtained to be 36.9 cm 2 /(V s) for the Dev. C. It was noticeable that there were marked differences in μ FE between the devices using ITO and Mo S/D electrodes.…”
Section: Resultsmentioning
confidence: 95%
“…It was typically found that the on-current ( I ON ) and μ FE values increased with increasing the In contents within the IGZO active channel layers for both sets of devices using ITO and Mo S/D electrodes. The threshold voltage ( V TH ) showed negative shifts as the increase in the In contents of the channel, which typically suggests that the conduction carriers might be additionally generated within In-richer IGZO channels. , The highest μ FE was obtained to be 36.9 cm 2 /(V s) for the Dev. C. It was noticeable that there were marked differences in μ FE between the devices using ITO and Mo S/D electrodes.…”
Section: Resultsmentioning
confidence: 99%
“…The most impressive feature was that the relative areal ratios of peaks A and B remarkably decrease and increase, respectively, as an increase in the deposition temperature. This implies that the ZnO thin films deposited at higher temperatures contain a larger number of oxygen-related defects, such as oxygen vacancies and weak metal-oxygen bonds [21,22]. The ALD reactions for the formation of ZnO thin films can be incompletely carried out at lower temperatures since the thermal energy required for the ALD reaction is relatively low and the degree of purge for residual H 2 O is insufficient.…”
Section: Resultsmentioning
confidence: 99%
“…% Al (AZO) were deposited by ALD at 150 and 180 °C as a gate insulator and a gate electrode, respectively, and patterned by wet chemical etching (Figures d,e). The fabricated devices were treated with postannealing process at 150 °C for 1 h in an oxygen atmosphere. Figure a shows a microscopic image of the fabricated flexible VTFT. The metal–semiconductor–insulator–metal (MSIM) capacitors were also fabricated on the same substrate to evaluate the electrical properties of the ALD-grown active layers and to elucidate feasible process damages.…”
Section: Methodsmentioning
confidence: 99%
“…The fabricated devices were treated with postannealing process at 150 °C for 1 h in an oxygen atmosphere. 24 Figure 2a shows a microscopic image of the fabricated flexible VTFT.…”
Section: Methodsmentioning
confidence: 99%